Solvent effects on the motion of a crown ether/amino rotaxane. Issue 47 (26th October 2022) - Wu, Zhen; Wang, Shuangshuang; Zhang, Zilin; Zhang, Yanjun; Yin, Yanzhen; Shi, Haixin; Jiao, Shufei
Abstract : A crown ether/amino rotaxane was investigated using two-dimensional free-energy landscapes to characterize the conformational change of the crown ether and the shuttling motions in chloroform and water. Abstract : Solvents have been recognized as a significant factor for modulating the shuttle of rotaxanes and regulating their functions regarding molecular machines by a lot of published studies. The mechanism of the effects of solvents on the motion of crown ether/amino rotaxanes, however, remains unclear. In this work, a rotaxane, formed by dibenzo-24-crown-8 (C[8]) and a dumbbell-shaped axle with two positively charged amino groups, was investigated at the atom level. Two-dimensional free-energy landscapes characterizing the conformational change of C[8] and the shuttling motions in chloroform and water were mapped. The results indicated that the barriers in water were evidently lower than those in chloroform. By analyzing the trajectories, there was no obvious steric effect during shuttling. Instead, the main driving force of shuttling was verified from electrostatic interactions, especially strong hydrogen bonding interactions between the axle and water, which resulted in the fast shuttling rate of the rotaxane. All in all, the polarity and hydrogen bond-forming ability of solvents are the main factors in affecting the shuttling rate of a crown ether/amino rotaxane. In addition, C[8] would adopt S-shaped conformations during shuttling except for situating in the amino sites with C-shaped ones adopted due to π–π stacking interactions. The results of this research improve the comprehension of the solvent modulation ability for shuttling in crown ether-based rotaxanes and illustrate the effects of structural modifications on motions. These new insights are expected to serve the efficient design and construction of molecular machines.